2018
DOI: 10.21037/apm.2018.07.04
|View full text |Cite
|
Sign up to set email alerts
|

Outcome measurement and complex physical, psychosocial and spiritual experiences of death and dying

Abstract: Patients with advanced illnesses, especially near the end of life, often experience multiple complex symptoms which may have profound impact on the quality of life of not only the patients but also their family members. Early and prompt recognition of such clinical challenges is linked with better end of life care for the dying patients, their caregivers and family members. In this narrative, which is not meant to be an in-depth systematic review, we attempt to provide an overview of some commonly used outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…[1][2][3][4][5] Timely recognition of clinical problems and initiation of adequate interventions are essential for patients and their families. [6][7][8][9] The systematic collection of patient-reported outcomes (PROs) with well-validated patient-reported outcome instruments can be an important component of symptom monitoring in routine palliative care that contributes to symptom control, allows for better use of health care resources, and results in improved quality of life and health. 8,10,11 However, while the importance of routine PRO assessments has been widely acknowledged, 8,10,11 a meta-analysis by Bush and colleagues suggested that they are still underutilized in palliative care.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Timely recognition of clinical problems and initiation of adequate interventions are essential for patients and their families. [6][7][8][9] The systematic collection of patient-reported outcomes (PROs) with well-validated patient-reported outcome instruments can be an important component of symptom monitoring in routine palliative care that contributes to symptom control, allows for better use of health care resources, and results in improved quality of life and health. 8,10,11 However, while the importance of routine PRO assessments has been widely acknowledged, 8,10,11 a meta-analysis by Bush and colleagues suggested that they are still underutilized in palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] The systematic collection of patient-reported outcomes (PROs) with well-validated patient-reported outcome instruments can be an important component of symptom monitoring in routine palliative care that contributes to symptom control, allows for better use of health care resources, and results in improved quality of life and health. 8,10,11 However, while the importance of routine PRO assessments has been widely acknowledged, 8,10,11 a meta-analysis by Bush and colleagues suggested that they are still underutilized in palliative care. 12 A critical aspect that has been highlighted in this context is the interpretation of PRO instruments, which is challenging for clinicians because of their perceived complexity and level of abstraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…P atients with advanced illnesses such as advanced refractory and terminal cancer, often experience multiple complex symptoms, 1 especially near end of life (EOL), which may have profound impact on the quality of life of patients and their family members. 2 Early and prompt recognition of such clinical challenges is linked with better endof-life care for the dying patients, their caregivers, and family members. 3 The well-being of family care-givers is of paramount importance due to the important role it plays in the well-being of a patient, including clarifying the goals of care (GOC).…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, biotechnological advances have led to substantial improvements in the biological attention to the human being. However, the psychological, social, and spiritual dimensions that, along with the biological, make up the individual have been disregarded (Azhar & Bruera, 2018).…”
mentioning
confidence: 99%